Women's narratives of health disruption and illness within and across their life stories - Hawkins, Jennifer M. editor; Kellett, Peter M. (Lexington studies in health communication, 2019)
Women's Narratives of Health Disruption and Illness: Within and Across Their Life Stories explores how women's broader and ongoing life stories impact--and are impacted by--health issues--back cover